Presenting a causal model of academic motivation based on self-fulfillment and self-regulation mediated by academic meaning in Corona pandemic conditions - Noorshahi, Nazanin; Tizdast, Taher; Rahmani, Mohammad Ali (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to present a causal model of academic motivation based on academic self-fulfillment, self-regulation mediated academic meaning in high school students in coronary pandemic conditions. Methods: The method of this cross-sectional study was correlational. The statistical population of this study consisted of all high school students in Tehran in 2019, of which 485 people (in modeling structural equations to determine the sample size can be between 5 to 15 observations per size variable multi-stage clusters were selected by random sampling method. The research instruments were: Harter (1981) Academic Motivation Questionnaire, Jones & Crandall (1968), Self-Regulatory Questionnaire, Pintrich et al. (1991) and Henderson-King and Smith (2006) Academic Meaning Questionnaire. In order to analyze the data, structural equation analysis software and SPSS-V23 and Lisrel-V8.8 software were used. Results: The results showed that academic self-fulfillment has a positive and significant effect on students' academic motivation (β=0.58, P